14 + 2x + 9x - 6 - 11x
14 - 6 + 2x + 9x - 11x
The x values cancel themselves out, leaving just the number value
The answer is therefore 8.
11x + 5y
2x2 + 11x + 12 = 2x2 + 3x + 8x + 12 = x*(2x + 3) + 4*(2x + 3) = (2x + 3)*(x + 4)
2x + 9x simplified would be 11x
2x2 + 11x + 15 = (x + 3)(2x + 5).
13x + 15 = 11x - 5 2x = -20 x = -10
-11x + 13
(2x - 7)(x - 2)
2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3
11x + 5y
2x2 + 11x + 12 = 2x2 + 3x + 8x + 12 = x*(2x + 3) + 4*(2x + 3) = (2x + 3)*(x + 4)
2x + 9x simplified would be 11x
13x+9
2x2 + 11x + 15 = (x + 3)(2x + 5).
6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)
2x
(x - 1)(2x - 9)
2x = 11x + 4 Subtract 11x from both sides: -9x = 4 Divide both sides by -9: x = 4/(-9) = -0.444...